1997
DOI: 10.1093/oxfordjournals.aje.a009070
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Exposures and Amyotrophic Lateral Sclerosis. A Population-based Case-Control Study

Abstract: This population-based case-control study was conducted in three countries in western Washington State to evaluate associations between workplace exposures and the risk of amyotrophic lateral sclerosis (ALS). Cases (n = 174) were all newly diagnosed with ALS by neurologists during 1990-1994, and controls (n = 348), who were matched according to age (+/-5 years) and sex, were identified via random-digit dialing or Medicare enrollment files. Four industrial hygienists blindly assessed detailed lifetime job histor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
140
3
5

Year Published

1998
1998
2016
2016

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 207 publications
(164 citation statements)
references
References 34 publications
16
140
3
5
Order By: Relevance
“…This method was applied using different time scales, including years before reference date, calendar year, and age. 28,29 Important residual confounding was not identified by age, nor was race (white or other) an important confounder. Given observed associations between education and case-control status and the likelihood of variation in use of dental services by education, we adjusted for education (schooling beyond high school or not).…”
Section: Analysesmentioning
confidence: 94%
“…This method was applied using different time scales, including years before reference date, calendar year, and age. 28,29 Important residual confounding was not identified by age, nor was race (white or other) an important confounder. Given observed associations between education and case-control status and the likelihood of variation in use of dental services by education, we adjusted for education (schooling beyond high school or not).…”
Section: Analysesmentioning
confidence: 94%
“…There was an increased risk of ALS among employees of the Dow Chemical Company who were exposed to the herbicide 2,4-dichlorophenoxyacetic acid versus other Dow employees (Burns et al, 2001). Similar studies have found positive associations for populations exposed to pesticides (McGuire et al, 1997;Qureshi et al, 2006), and the relationship was found to be dependent on dose (Morahan & Pamphlett, 2006). Overall, the relationship tends to be stronger for males than females (McGuire et al, 1997;Morahan & Pamphlett, 2006).…”
Section: Amyotrophic Lateral Sclerosis (Als)mentioning
confidence: 65%
“…Similar studies have found positive associations for populations exposed to pesticides (McGuire et al, 1997;Qureshi et al, 2006), and the relationship was found to be dependent on dose (Morahan & Pamphlett, 2006). Overall, the relationship tends to be stronger for males than females (McGuire et al, 1997;Morahan & Pamphlett, 2006). In one study using participants in the American Cancer www.intechopen.com Society's Cancer Prevention Study II, no association between pesticide exposure and ALS was detected (Weisskopf et al, 2009).…”
Section: Amyotrophic Lateral Sclerosis (Als)mentioning
confidence: 72%
“…McGuire et al 27 saw associations, but no dose-response trends, between ALS and the occupational use of cleaning solvents/degreasers as well as alcohols and ketones; however, they found no association between ALS and solvent usage overall. They did, however, find an unexpected association between ALS and insecticides/agricultural chemicals.…”
Section: Work Historymentioning
confidence: 95%
“…Care must be taken when interpreting the results of many ALS risk factor studies, as most employ a case-control design and depend largely upon subject recall to measure past exposures. Indeed, a couple of studies based on independent, third-party characterizations of past exposures, particularly those related to occupation, found no significant associations between the studied exposures and ALS.26, 27 …”
Section: -25mentioning
confidence: 99%